An introduction to matched filters - Turin, G. (I.R.E. transactions on information theory, 1960)
In a tutorial exposition, the following topics are discussed: definition of a matched filter; where matched filters arise; properties of matched filters; matched-filter synthesis and signal specification; some forms of matched filters.